Plan de marketing, para el canal institucional de la empresa Productos Familia Sancela del Ecuador S.A. - Lescano Lara, Yessenia Katherine (2018)
The consumption of hygiene and cleaning implements are increasingly products with greater demand by industries because their own requirements, it is convenient to have specific products for them where they guarantee a good use by their staff and watch over the economy of the company. Analyzing the channel of Institutional Family, this channel is specifically responsible for everything related to hygiene and cleanliness at the company level and every day ensures the development of new products with an adequate performance for companies that allows them to economize in these aspects. The great inconvenience that remains so far is that there has been a marketing plan that can be achieved. That is why the marketing plan is made in order to achieve customer loyalty and increase sales of the company. When carrying out market research, we can establish that there is a great possibility of customer loyalty because they feel that they lack information from the company. This is why the creation of a website of the Institutional Family at the Ecuadorian level is proposed, because the page that is currently in force does not help the clients because it offers the products and information of Colombia. When preparing the web page where all the information about the company will be provided, it also facilitates the creation of an e-commerce that facilitates new people interested in the products to be able to acquire them quickly. Through a financial analysis, it was possible to determine that the project is profitable for the brand so it corroborates in the implementation of the same as a new sales area within the scheme that manages the brand.